CELL TO CELL INTERACTION IN THE IMMUNE RESPONSE : V. TARGET CELLS FOR TOLERANCE INDUCTION - Miller, J. F. A. P. (The Rockefeller University Press, 1970)
Collaboration between thymus-derived lymphocytes, and nonthymus-derived antibody-forming cell precursors occurs during the immune response of mice to sheep erythrocytes (SRBC). The aim of the experiments reported here was to attempt to induce tolerance in each of the two cell populations to determine which cell type dictates the specificity of the response. Adult mice were rendered specifically tolerant to SRBC by treatment with one large dose of SRBC followed by cyclophosphamide. Attempts to restore to normal their anti-SRBC response by injecting lymphoid cells from various sources were unsuccessful. A slight increase in the response was, however, obtained in recipients of thymus or thoracic duct lymphocytes and a more substantial increase in recipients of spleen cells or of a mixture of thymus or thoracic duct cells and normal marrow or spleen cells from thymectomized donors. Thymus cells from tolerant mice were as effective as thymus cells from normal or cyclophosphamide-treated controls in enabling neonatally thymectomized recipients to respond to SRBC and in collaborating with normal marrow cells to allow a response to SRBC in irradiated mice. Tolerance was thus not achieved at the level of thelymphocyte population within the thymus, perhaps because of insufficient penetration of the thymus by the antigens concerned. By contrast, thoracic duct lymphocytes from tolerant mice failed to restore to normal the response of neonatally thymectomized recipients to SRBC. Tolerance is thus a property that can be linked specifically to thymus-derived cells as they exist in the mobile pool of recirculating lymphocytes outside the thymus. Thymus-derived cells are thus considered capable of recognizing and specifically reacting with antigenic determinants. Marrow cells from tolerant mice were as effective as marrow cells from cyclophosphamide-treated or normal controls in collaborating with normal thymus cells to allow a response to SRBC in irradiated recipients. When a mixture of thymus or thoracic duct cells and lymph node cells was given to irradiated mice, the response to SRBC was essentially the same whether the lymph node cells were derived from tolerant donors or from thymectomized irradiated, marrow-protected donors. Attempts to induce tolerance to SRBC in adult thymectomized, irradiated mice 3–4 wk after marrow protection, by treatment with SRBC and cyclophosphamide, were unsuccessful: after injection of thoracic duct cells, a vigorous response to SRBC occurred. The magnitude of the response was the same whether or not thymus cells had been given prior to the tolerization regime. The various experimental designs have thus failed to demonstrate specific tolerance in the nonthymus-derived lymphocyte population. Several alternative possibilities were discussed. Perhaps such a population does not contain cells capable of dictating the specificity of the response. This was considered unlikely. Alternatively, tolerance may have been achieved but soon masked by a rapid, thymus-independent, differentiation of marrow-derived lymphoid stem cells. On the other hand, tolerance may not have occurred simply because the induction of tolerance, like the induction of antibody formation, requires the collaboration of thymus-derived cells. Finally, tolerance in the nonthymus-derived cell population may never be achieved because the SRBC-cyclophosphamide regime specifically eliminates thymus-derived cells leaving the antibody-forming cell precursors intact but unable to react with antigen as there are no thymus-derived cells with which to interact.